Functional Performance Testing After Anterior Cruciate Ligament Reconstruction: A Systematic Review. Issue 1 (19th January 2014) - Abrams, Geoffrey D.; Harris, Joshua D.; Gupta, Anil K.; McCormick, Frank M.; Bush-Joseph, Charles A.; Verma, Nikhil N.; Cole, Brian J.; Bach, Bernard R.
Background: When to allow an athlete to return to unrestricted sporting activity after anterior cruciate ligament (ACL) reconstruction remains controversial. Purpose: To report the results of functional performance testing reported in the literature for individuals at differing time points following ACL reconstruction and to examine differences between graft types. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review of Medline, Scopus, and Cochrane Central Register of Controlled Trials was performed using PRISMA guidelines. Inclusion criteria were English-language studies that examined any functional rehabilitation test from 6 months to 2 years following ACL reconstruction. All patient-, limb-, and knee-specific demographics were extracted from included investigations. All functional rehabilitation tests were analyzed and compared when applicable. Results: The search term returned a total of 890 potential studies, with 88 meeting inclusion and exclusion criteria. A total of 4927 patients were included, of which 66% were male. The mean patient age was 26.5 ± 3.4 years. The predominant graft choices for reconstruction were bone–patellar tendon–bone (BPTB) autograft (59.8%) and hamstring autograft (37.9%). The most commonly reported functional tests were the hop tests. The results of these functional tests, as reported in the Limb Symmetry Index (LSI), improved with increasing time, with nearly all results greater than 90% at 1 year following primary ACL reconstruction. At 6 months postoperatively, a number of isokinetic strength measurements failed to reach 80% LSI, most commonly isokinetic knee extension testing in both BPTB and hamstring autograft groups. The knee flexion strength deficit was significantly less in the BPTB autograft group as compared with those having hamstring autograft at 1 year postoperatively, while no significant differences were found in isokinetic extension strength between the 2 groups. Conclusion: Hop testing was the most commonly reported functional test following ACL reconstruction. Increases in performance on functional tests were predictably seen as time increased following surgery. Those with hamstring autografts may experience increased strength deficits with knee flexion versus those having BPTB autograft. These data provide information that may assist providers in determining timing of return to unrestricted sporting activity.